LARP7 Protects Against Heart Failure by Enhancing Mitochondrial Biogenesis. Issue 20 (18th May 2021) - Yu, Huijing; Zhang, Fang; Yan, Pengyi; Zhang, Shasha; Lou, Yingmei; Geng, Zilong; Li, Zixuan; Zhang, Yan; Xu, Yuejuan; Lu, Yanan; Chen, Chen; Wang, Daowen; et al.
Abstract : Background: Heart failure (HF) is among the leading causes of morbidity and mortality, and its prevalence continues to rise. LARP7 (La ribonucleoprotein domain family member 7) is a master regulator that governs the DNA damage response and RNAPII (RNA polymerase II) pausing pathway, but its role in HF pathogenesis is incompletely understood. Methods: We assessed LARP7 expression in human HF and in nonhuman primate and mouse HF models. To study the function of LARP7 in heart, we generated global and cardiac-specific LARP7 knockout mice. We acutely abolished LARP7 in mature cardiomyocytes by Cas9-mediated LARP7 somatic knockout. We overexpressed LARP7 in cardiomyocytes using adeno-associated virus serotype 9 and ATM (ataxia telangiectasia mutated protein) inhibitor. The therapeutic potential of LARP7-regulated pathways in HF was tested in a mouse myocardial infarction model. Results: LARP7 was profoundly downregulated in failing human hearts and in nonhuman primate and murine hearts after myocardial infarction. Low LARP7 levels in failing hearts were linked to elevated reactive oxygen species, which activated the ATM-mediated DNA damage response pathway and promoted LARP7 ubiquitination and degradation. Constitutive LARP7 knockout in mouse resulted in impaired mitochondrial biogenesis, myocardial hypoplasia, and midgestational lethality. Cardiac-specific inactivation resulted in defective mitochondrial biogenesis, impaired oxidative phosphorylation, elevated oxidative stress, and HF by 4 months of age. These abnormalities were accompanied by reduced SIRT1 (silent mating type information regulation 2 homolog 1) stability and deacetylase activity that impaired SIRT1-mediated transcription of genes for oxidative phosphorylation and energy metabolism and dampened cardiac function. Restoring LARP7 expression after myocardial infarction by either adeno-associated virus–mediated LARP7 expression or small molecule ATM inhibitor substantially improved the function of injured heart. Conclusions: LARP7 is essential for mitochondrial biogenesis, energy production, and cardiac function by modulating SIRT1 homeostasis and activity. Reduction of LARP7 in diseased hearts owing to activation of the ATM pathway contributes to HF pathogenesis and restoring LARP7 in the injured heart confers myocardial protection. These results identify the ATM-LARP7-SIRT1 pathway as a target for therapeutic intervention in HF. Abstract : Supplemental Digital Content is available in the text.